Integrating fire spread patterns in fire modelling at landscape scale. (December 2016) - Duane, Andrea; Aquilué, Núria; Gil-Tena, Assu; Brotons, Lluís
Abstract: Fire spread modelling in landscape fire succession models needs to improve to handle uncertainty under global change processes and the resulting impact on forest systems. Linking fire spread patterns to synoptic-scale weather situations are a promising approach to simulating fire spread without fine-grained weather data. Here we present MedSpread—a model that evaluates the weights of five landscape factors in fire spread performance. We readjusted the factor weights for convective, topography-driven and wind-driven fires (n = 123) and re-assessed each fire spread group's performance against seven other control simulations. Results show that for each of the three fire spread patterns, some landscape factors exert a higher influence on fire spread simulation than others. We also found strong evidence that separating fires by fire spread pattern improves model performances. This study shows a promising link between relevant fire weather information, fire spread and fire regime simulation under global change processes. Highlights: We used fire spread patterns to simulate fire spread in landscape succession models. Modelling fire spread patterns improved simulations of fire propagation. Factors governing fire spread differed among topographic, convective and wind fires. Synoptic weather situations can populate fire spread modelling at large spatial scales.